The effectiveness of pulmonary rehabilitation in COPD patients to re-admission rate from exacerbations within 1 year - Khamkruang, Jirawan; Tepsing, Pawinee; Thongbai, Natthathida (Journal of Phrae Public Health for Development - วารสารสาธารณสุขแพร่เพื่อการพัฒนา, 2024)
This quasi-experimental research aimed to study the effectiveness of physiotherapists' pulmonary rehabilitation in patients with chronic obstructive pulmonary disease (COPD) in the rate of hospital readmissions due to exacerbations within one year. The sample consisted of 40 conveniently selected COPD patients. The research tools included a pulmonary rehabilitation program. Data collection instruments were the Pulmonary Rehabilitation Checklist, the 6-Minute Walk Test for assessing daily activity capability form, and the quality-of-life form. The content validity of the Pulmonary Rehabilitation Checklist was 0.93, and the intra-examiner reliability of the three assessment tools was good (ICC = 0.80). Data were analyzed using descriptive statistics, paired sample t-tests, and Pearson correlation coefficient. The study found that all 40 COPD patients who participated in the program had an average age of 70.63 years and an average body mass index (BMI) of 19.19. Of these, 87.50% correctly followed the pulmonary rehabilitation program. Statistical analysis showed significant differences in daily activity capability, quality of life, and the rate of hospital readmissions due to exacerbations within one year before and after participating in the pulmonary rehabilitation program (p < 0.001). After completing the program, patients showed improved daily activity capability, better quality of life, and a tendency for reduced hospital readmissions due to exacerbations compared to before participating in the rehabilitation activities.